Hydrogen diffusion coefficient in monoclinic zirconia in presence of oxygen vacancies. (12th September 2022) - Haurat, Emile; Crocombette, Jean-Paul; Schuler, Thomas; Tupin, Marc
Abstract: To better understand the hydrogen diffusion mechanisms in monoclinic zirconia that take place in fuel rod cladding during reactor operation, we calculate the diffusion paths of different defects involving hydrogen and oxygen vacancies using Density Functional Theory with hybrid functionals, and use them to obtain the hydrogen and oxygen diffusion coefficients. We find a hydrogen diffusion coefficient varying between 10 −10 to 10 −20 cm 2 ⋅s − 1 at 600 K, strongly depending on the hydrogen to oxygen vacancy ratio. We find that the interstitial hydrogen atoms are the main diffusing species even though they are not the dominant configuration of hydrogen atoms. We confirm the existence of different huge trapping effects, which slow the hydrogen diffusion. The main mechanism is either the trapping of hydrogen atoms in oxygen vacancies or the formation of interstitial dihydrogen molecules depending on the hydrogen to oxygen vacancy ratio. Graphical abstract: Image 1 Highlights: Interstitial hydrogen molecules are stable in zirconia, but do not diffuse. Interstitial hydrogen atoms are the diffusing species but not the most concentrated. Oxygen vacancies have a huge trapping effect on hydrogen atoms. The hydrogen to oxygen vacancy concentration ratio controls the diffusion coefficient.